Minimizing the Risk in Investment Projects - Nazari, Reza (European Journal of Sustainable Development, 2017)
Investors must consider and explore two main parameters which are efficiency and its risk in investing and forming the optimal portfolio and select the optimal portfolio in base of these two parameters, and also by attention to these parameters try to optimize the two-parameter model. Through the present research, the quality of forming the different portfolios from diverse stocks for minimizing the risk of portfolios collection was explored. The hypothesis is that each portfolio’s risk formed from a collection of different stock risk is stated as the identified function. The identified function just depends on the investment’s value which was done for considered portfolio’s forming and the total portfolio’s risk is a function of collection of separated risks of components of that portfolio. The main discussion of the present research is the nonlinear minimizing two-parameter which can be changed as a minimizing one-parameter issue for different identified goal function. The functioned researches have proved the optimizing two-parameter model both weakly and strongly by ignoring one of the parameters. Changing the two-parameter-optimizing issue as the single-parameter issue is one by the usefulness functions and risk. Key Words: Financial Markets, Specifying Optimal Attribution, Forming the Portfolio, Two-Criteria Issues, Single-Criterion Issues, Goal Function, Complete Risk.